Evolution of the carbonate state of agrogenically transformed dark gray forest soils in the central forest-steppe - Kuznetsova, A. M.; Khokhlova, O. S.; Chendev, Yu. G.; Aleksandrovskii, A. L. (Eurasian soil science, 2010)
The integrated study of the carbonate state of soils, which involves all the forms of soil carbonates at different levels of the soil organization, allows exactly assessing the degree and the rate of the soil transformation due to agricultural development. The evolution of the carbonate state in agrogenically transformed soils was assessed on a site with a known land-use history and with remaining natural soils. The direction, rate, and stages of the carbonate state transformation upon the agrogenic use of dark gray forest soils were determined on the basis of the morphogenetic analysis. Agricultural development entails a significant reorganization of the carbonate profile: a dark gray forest soil evolves into a medium-thick slightly podzolic chernozem with a greater pool of carbonates. The calcareous pedofeatures and horizons evolve stepwise: in the soil of a 100-year-old plowland, the transition to another organization of the carbonate state is observed: carbonates migrate more actively, and the dissolution-precipitation conditions are most dynamic. In the upper calcareous horizons, the structure of the calcitic pedofeatures becomes more collomorphic, and this mass fills almost all the voids; in the lower calcareous horizons, calcite is predominantly segregated into calcareous pedofeatures.